Hubungan Tata Kelola Baik dan Manajemen Laba: Pendekatan Quality Accrual - Wenny Febriyanti; Negina Kencono Putri; Eko Suyono (Department of Accounting-Faculty of Economic and Business (FEB), 2016)
The purpose of this study is to determine the effect of good corporate governance (GCG) which includes the audit committee, independent commissioners, and executive compensation to earnings management. Sample of this research are 34 financial statements of several manufacturing companies in the automotive and pharmaceutical companies which go public in Indonesia Stock Exchange in 2008 to 2014. Researcher use multiple regression to analyze the data research. The results of this study states that the audit committee, independent commissioners and executive compensation doesn’t have an effect to earnings management in automotive and pharmaceutical companies in Indonesia. Finally, the research is expected to provide insights into the good corporate governance and earnings management in the automotive and pharmaceutical companies which go public in Indonesia Stock Exchange.